2013
DOI: 10.1007/s00299-013-1440-3
|View full text |Cite
|
Sign up to set email alerts
|

Promoter analysis of the WRKY transcription factors CaWRKY1a and CaWRKY1b homoeologous genes in coffee (Coffea arabica)

Abstract: The regulation of the CaWRKY1 homoeologous genes were analyzed through the characterization of their promoters. The pW1a promoter is proposed as a new tool for coffee plant biotechnologies. WRKY transcription factors are important elements of the plant immune response. The CaWRKY1 gene from Coffea arabica is induced by several biotic and abiotic stresses, including challenge by the rust fungus Hemileia vastatrix. Two homoeologous CaWRKY1 genes, named CaWRKY1a and CaWRKY1b, were previously identified in the C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In agreement with the W-box enrichment in their own promoters, it has been demonstrated that the WRKY proteins act on the promoters of their own genes and on other WRKY genes in cotransfection assays resulting in activation or repression of a reporter gene (Robatzek and Somssich, 2002; Petitot et al, 2013; Potschin et al, 2013). In addition, a pull-down analysis of WRKY53 with genomic DNA resulted in a list of putative target genes of WRKY53 including eight different WRKY genes (Miao et al, 2004).…”
Section: The Wrky Tfs and Their Regulationmentioning
confidence: 56%
See 1 more Smart Citation
“…In agreement with the W-box enrichment in their own promoters, it has been demonstrated that the WRKY proteins act on the promoters of their own genes and on other WRKY genes in cotransfection assays resulting in activation or repression of a reporter gene (Robatzek and Somssich, 2002; Petitot et al, 2013; Potschin et al, 2013). In addition, a pull-down analysis of WRKY53 with genomic DNA resulted in a list of putative target genes of WRKY53 including eight different WRKY genes (Miao et al, 2004).…”
Section: The Wrky Tfs and Their Regulationmentioning
confidence: 56%
“…For example, two W-boxes were found in the promoter of AtWRKY6 , four and five W-boxes in the promoters of the two homologous genes of Coffea arabica , five W-boxes in the promoter of AtWRKY18 , and three perfect W-boxes plus an additional TGAC cluster in the promoter of AtWRKY53 (Robatzek and Somssich, 2001; Petitot et al, 2013; Potschin et al, 2013). Some WRKYs even carry 11 or 12 ( AtWRKY66 , AtWRKY17 ) TTGAC core elements in an analyzed 1.5 kb promoter fragment (Dong et al, 2003).…”
Section: The Wrky Tfs and Their Regulationmentioning
confidence: 99%
“…The cloning of genes involved in the SE process, with the goal of increasing the efficiency of the process (Arroyo-Herrera et al 2008), and the production of plants with resistance to different kind of stresses (Leroy et al 1999(Leroy et al , 2000Perthuis et al 2005). During the last years our knowledge on coffee pests and disease resistance genes (Lashermes et al 2010;Noir et al 2003;Ribas et al 2011b), drought resistance genes (Marraccini et al 2011), and specific promoters (Marraccini et al 1999;Petitot et al 2013) has made possible to target specific genes to improve Coffea spp.…”
Section: Agrobacterium Tumefaciensmentioning
confidence: 98%
“…In many cases, comparative genomics leads to new findings in agriculturally and economically important crops (Marchive et al 2007;Mare et al 2004;Petitot et al 2013;Shekhawat et al 2011). Recently, Luo et al (2013) have described that in wild soybean, Glycine soja, GswRKY20 promotes the expression of negative regulators of ABA signaling while repressing positive regulators.…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%